Congenital Nephrotic Syndrome: A Cases Report - Saeedreza Lotfi; Ashraf Mohammdzadeh; Ahmadshah Farhat; Reza Saeidi; Mirfarhad Mirmohammadi (Mashhad University of Medical Sciences, 2018)
Congenital nephrotic syndrome (CNS) can be caused by neonatal infections and renal diseases that usually occur in early infancy. The most common CNS is the Finnish type, which is an autosomal recessively inherited disease characterized by intrauterine onset of massive proteinuria. In this study, we presented a preterm neonate confirmed as the first case of CNS in Iran by genetic study, who was admitted to the Neonatal Intensive Care Unit of Imam Reza Hospital, Mashhad, Iran. The patient's mother had gestational diabetes mellitus and a history of intrahepatic cholestasis of pregnancy. The newborn was hospitalized at birth because of hypoglycemia. Upon admission, repeat seizure, intraventricular hemorrhage, intracerebral hemorrhage, and edema (specific gravity of more than 58 and sever protein urea) were detected. Furthermore, hypoalbuminemia was observed. The result of the blood culture and cerebral spinal fluid culture were negative. In addition, TORCH and venereal disease research laboratory tests were negative. Finally, genetic study showed a mutation in C3250 DUPG.